A Critique of Deep Ecology - Chris Abakare (Indonesian Journal of Social and Educational Studies, 2021)
Deep ecology, in its broad meaning, is used by Naess to refer to the broad ecocentric grass-root effort as contrasted with an anthropocentric approach to achieve an ecologically balanced future. Deep ecology embraces a deep approach by speaking about the intrinsic value of nature. In this connection, Naess advocates the principle of biospheric egalitarianism claiming equal moral worth of all beings, human and non-human alike. It is an approach of realising man’s position in the larger web of things. In practice, deep ecology is a movement which is concerned with the solution of grass-root social and political problems for an ecologically sustainable future. In principle, it upholds a holistic view of nature transcending the narrow ego-centric self that undertakes a thesis of Self-realization or identifying oneself with the greater ecological-Self. This work is a critical study of the deep ecology philosophy. The basic focus of this work, centres around the debate among the different schools of environmental philosophy, particularly, the criticism of deep ecology by social ecology.